The frequency of outcomes of viral meningitis and meningoencephalitis in children depends on the duration of medical supervision - O. G. Kimirilova; G. A. Kharchenko (Лечащий Врач, 2025)
Background. It has been found that even mild forms of viral meningitis can have in the outcome of the disease the presence of neurologic deficits that remain undetected at the time of patient discharge from hospital and during follow-up. Consequences of viral neuroinfections (meningitis, meningoencephalitis) they occur quite often in children and not only in patients with severe forms of the disease.Objective. The aim of the study was to determine the frequency of outcomes of viral meningitis and meningoencephalitis in children, depending on the duration of medical supervision.Materials and methods. A prospective single-center observational cohort study was conducted. The cohort included 60 patients selected by simple randomized nonrepeatable method, including 50 (83.3%) who had viral meningitis and 10 (16.7%) who had meningoencephalitis. The outcomes of viral meningitis and meningoencephalitis were studied in 28 (46.7%) of moderate and 32 (53.3%) of severe forms of the disease, aged 7.6 ± 1.5 years within 36 months after the disease, and in 75% of patients in this group after 10 years, aged 16.9 ± 0.8 years.Results. It was found that the predominant outcomes, 6 months after viral meningitis and meningoencephalitis, were: cerebrasthenia, hypertension syndrome, vegetative dystonia in 91.7%, severe neurological deficit in 4 (6.7%) patients. By the end of the late recovery period (36 months), neurological disorders persisted in 25%, including irreversible in 4 (6.7%) of the 60 children in the catamnesis group. Memory impairments in patients with viral meningitis were short-lived and occurred only during the period of early convalescence, unlike other disease outcomes that developed after 24 months or more (migraine, associated, epileptic reactions) and persisted even 10 years after meningitis. The incidence of vegetative dystonia in adolescents who had viral meningitis at the age of 7-8 years increased to 40% and was more often of a mixed type.Conclusion. An increase in the number of patients with neurological deficits in the catamnesis group indicates the possibility of its development and manifestation in children discharged from the hospital with clinical and laboratory recovery at various times of the convalescence period.